The Influence of Consumer Perceptions on Cross-Buying Intention among Apple Product Users in Pekanbaru City - Maulana, Andre; Afwa, Awliya; Moniko, Moniko; Hadi, Hamanda (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study examined the determinants of cross-buying intention within Apple’s product ecosystem among users in Pekanbaru, Indonesia. A quantitative explanatory survey with a deductive design was used to test theory-driven relationships between consumer perceptions and cross-category purchase intentions. Data were collected online from 177 participants; after residency screening, 160 valid responses remained. Constructs comprised perceived product benefit, perceived price attractiveness, perceived convenience, perceived product fit, perceived aesthetic quality, and cross-buying intention. Measurement and structural assessments were conducted using Partial Least Squares Structural Equation Modeling. The measurement model satisfied accepted thresholds for internal consistency, convergent validity, and discriminant validity, and diagnostics indicated no substantive bias from a single measurement source. Structural results showed that perceived aesthetic quality and perceived price attractiveness positively influenced cross-buying intention, whereas perceived convenience, perceived product benefit, and perceived product fit were not significant. The model explained a substantial share of variance in cross-buying intention, indicating strong explanatory power. Overall, the findings suggested that emotional–symbolic value—particularly design coherence and the perception of price as a signal of quality—played a more decisive role than purely functional considerations in motivating cross-category expansion within a premium brand ecosystem. Managerial implications and avenues for future research were outlined.